Amphibians of grasslands in the state of Paraná, southern Brazil (Campos Sulinos) - Crivellari, Lucas Batista [UNESP]; Leivas, Peterson Trevisan; Leite, Julio César Moura; Gonçalves, Darlene da Silva; Mello, Caio Marinho; Rossa-Feres, Denise de Cerqueira [UNESP]; Conte, Carlos Eduardo (My University, 2014)
Amphibian conservation depends on knowledge about species composition and distribution. This emphasizes the need for inventories, especially in poorly sampled areas. This is the case of Southern grasslands (Campos Sulinos) associated with Araucaria forest in the state of Paraná, southern Brazil. We sampled amphibians in 105 environments from 2004 to 2013 using transect sampling, active search and surveys at breeding sites. We found 61 anuran species and two caecilians. This is the first comprehensive list of amphibian species inhabiting grasslands in Paraná. This landscape deserves high conservation priority before these natural grasslands vanish.
Keywords: Anura; regional pool diversity; geographic distribution; inventory